PENGENDALIAN WAKTU DAN BIAYA PELAKSANAAN PROYEK PEMBANGUNAN UNIT LAYANAN KANKER TERPADU RSUD BALI MANDARA - Dharmayanti, Gusti Ayu Putu Candra; Diputra, Gede Astawa; Damayanthi, Ni Putu Eka Rahayu (Jurnal Ilmiah Teknik Sipil, 2022)
The construction of the Integrated Cancer Service Unit of Mandara Regional Hospital experienced a delay in employment in the 10th week of 1,16%, the 11th week of 2,58%, and the 12th week of 3,77%, so the project control action required to overcome the problem. This study aimed to evaluate the project performance interm of cost and time. In this study used secondary data consisting of, budget plan, project drawings, project progress reports, and time schedule. The implementation budget plan value is calculated based on the unit price analysis and the contractor’s cost budget plan excluding tax and profit (implementation budget plan = Rp 45,917,529,226.76). Earned Value method includes indicators consisting of Actual Cost of Work Perfomanced (ACWP), Budgeted Cost of Work Perfomanced (BCWP), and Budgeted Cost of Work Scheduled (BCWS) are used to determine the parameters that show project performance such as schedule and cost variance, schedule and cost perfomanced index,  and can provide the final condition information of the project. The results of the project performance evaluation in Week 12, based on the aspect of the cost, showed the estimated cost for the remaining work (ETC) of Rp 39.646.437.551,40 and estimated costs required until the end of the project (EAC) amounting to Rp 46.270.139.788,49, increasing the project costs of Rp 352.610.561,73. From the time aspect, the project is predicted to finish with time (EAS) 34,74 weeks, while the remaining time to complete the project (ETS) is 22,74 weeks. The time exceeded the planned time of 30 weeks (time schedule), so the predicted project had a delay of 4,74 weeks. Accordingly,  rescheduling is conducted for the rest of the activities  using Microsoft Project software involving 3 hours overtime per day on 66 work items that are on the critical track, therefore the project can be completed as the planned time.